Drug-associated hearing impairment in children: a disproportionality analysis of the FDA adverse event reporting system - Liu, Jinfeng; Tan, Junyi; Xiao, Qinli; Bai, Yingtao; Chang, En; Su, Chun; Wei, Yuxun; Zhong, Hu; Wei, Wei (Frontiers in Pharmacology, 2025)
ObjectiveDrug-associated hearing impairment has a serious impact on children’s quality of life and poses a significant public health burden. However, there is a lack of large-scale population-based studies of medication-associated hearing impairment in children. The aim of this study was to hypothesize about medications through data mining in order to assess the potential risk of these medications increasing hearing impairment in children.MethodsWe extracted and analyzed reports on drugs linked to hearing impairment in children from the FDA Adverse Event Reporting System (FAERS). To assess the relationship between drugs and hearing impairment in children, we performed a disproportionality study utilizing the proportional reporting ratio (PRR) and reporting odds ratio (ROR). Concurrently, we conducted comparisons with medicine labels to identify medications that, although not now indicating hearing impairment in their labels, may possibly pose risks of hearing impairment in children.ResultsIn the FAERS database, there are 1,884 reports of AE related to hearing impairment in children. The top three medications with the highest ROR were vinblastin [N = 6 cases, ROR = 86.72 (34.15–220.19)], risedronate [N = 3 cases, ROR = 73.59 (20.24–267.63)], and amikacin [N = 11 cases, ROR = 71.31 (36.40–139.72)]. The top 3 drugs with the highest number of reports were carboplatin [N = 125 cases, ROR = 18.41 (15.27–22.21)], cisplatin [N = 78 cases, ROR = 31.24 (24.59–39.70)], and vincristine [N = 56 cases, ROR = 6.32 (4.83–8.27)]. Based on drug labeling, 48% drugs (27/56) were classified as potentially ototoxic.ConclusionOur findings suggest that nearly half of the 56 drugs linked to hearing impairment signals in children are not currently labeled with ototoxicity warnings. Consequently, further research is required to evaluate the association of these medicines with this risk.